ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI - MEILYANA, ELIZABETH (Berkala Ilmiah Mahasiswa Akuntansi)
The purpose of this research is to examine the influence of mechanism application corporate governance which involves the proportion of institutional ownership and proportion of independent board members and also the influence of the earnings management to company’s value. This research took 47 samples from manufacture industry in Bursa Efek Indonesia in period 2008-2010. The samples were taking by using purposive sampling method. This research is using linier regression analysis, which is doubled linier regression to know the mechanism of two variables corporate governance to earnings management and company value and also to know the influence of earnings management to company value. The counting and hypothesis testing were conducted using SPSS 13. The result from this research shows that the proportion of institutional ownership and the proportion of the amount of member’s commissioner council do not give significance influence to the earnings management which using Discretionary Accrual. The same with the research result from the proportion of institutional ownership and the proportion of the amount of member’s commissioner council which shows no influence to company value. But, the result of earnings management to company value shows that there is significance influence.